Aldo-keto reductase and alcohol dehydrogenase contribute to benznidazole natural resistance in Trypanosoma cruzi - González, Laura (2017)
Fil: Gonzalez, Laura. Universidad de Antioquia. Grupo de Biología y Control de Enfermedades Infecciosas-BCEI; Colombia.